2014
DOI: 10.1208/s12249-014-0229-1
|View full text |Cite
|
Sign up to set email alerts
|

Bilayer Matrix Tablets for Prolonged Actions of Metformin Hydrochloride and Repaglinide

Abstract: A combination therapy of metformin hydrochloride (MH) and repaglinide (RG) achieves a perfect glycemic control; however, the combination formulation of immediate release must be taken several times a day, compromising the therapeutic benefits and causing inconveniences to the patients. Herein, a bilayer matrix tablet that aimed at continuously releasing both MH and RG over time was developed, in which the two drugs were formulated into two separated layers. The tablets were prepared by wet granulation method, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Formulations F3 and F4 also include NaCMC to granulate the metformin HCl and it contributes to stabilize the gel layer. The presence of NaCMC increased the robustness and resistance of the hydrated gel layer of the matrices [33].…”
Section: Discussionmentioning
confidence: 99%
“…Formulations F3 and F4 also include NaCMC to granulate the metformin HCl and it contributes to stabilize the gel layer. The presence of NaCMC increased the robustness and resistance of the hydrated gel layer of the matrices [33].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the release profiles obtained for tablets 4 and 5 need to be investigated for commercial utilization from the point of view of oral absorbability. He et al [14] revealed that sustained-release tablets containing metformin and repaglinide showed bioavailabilities equal to those of rapid-release tablets in in vivo studies with beagle dogs. Metformin and repaglinide are used for models of water-soluble and poorly water-soluble drug compounds, respectively; the sustained-release tablets exhibited release profiles similar to our data obtained in vitro.…”
Section: Formulation and Characterization Of Controlled-release Table...mentioning
confidence: 99%
“…The hydration rate increases with the amount of hydroxypropyl, which can slowly dissolve in cold water, as it is a viscous solution. By utilizing these characteristics, HPMC was incorporated into the inside of a tablet for sustained-release systems, the efficacy of which was supported by several studies in vitro and in vivo [9,13,14]. However, it has not yet been reported whether the HPMC-containing tablets reached the lower-intestinal sites between the ileum and colon.…”
Section: Introductionmentioning
confidence: 99%
“…7 These formulations were reported to improve the relative bioavailability of REP around 111% to 113% compared to oral bolus. Further, bilayer matrix tablets for prolonged release of metformin hydrochloride and REP, 8 gastro retentive drug delivery of REP through mucoadhesive tablets, 9 floating microspheres, 10,11 mucoadhesive microsphere 12 and mucoadhesive nanoparticles 13 were reported. Yet, those formulations could not overcome the first-pass effect of REP due to GIT is being their common site of administration.…”
Section: Introductionmentioning
confidence: 99%